Recuperación urbano paisajística del parque Rafael Uribe como espacio turístico y cultural en Honda - Tolima (2024)
Honda, Tolima, faces various issues associated with the deterioration of its urban infrastructure, social disconnection, lack of adequate public spaces, and the need to boost its local economy through tourism. These conditions affect the quality of life of its residents and limit the city’s potential as a tourist destination, despite its rich historical and cultural heritage. In response to this situation, an urban-landscape recovery project is proposed for Rafael Uribe Uribe Park, aimed at developing a new riverside walkway along the environmental axis of the Gualí River. This initiative seeks to revitalize Honda’s tourist appeal while strengthening its urban fabric and social connectivity. The project not only addresses existing issues but also aims to position Honda as an example of sustainable tourism and public space recovery in urban-heritage contexts.